Application of Claisen Rearrangement and Olefin Metathesis in Organic Synthesis. Issue 14 (29th June 2018) - Kotha, Sambasivarao; Meshram, Milind
Abstract: Several new synthetic methods to diverse polycycles and heterocycles on the basis of [3, 3]‐sigmatropic rearrangement and ring‐closing metathesis as key steps are summarized. In this regard, Claisen, aza‐Claisen, and Overman rearrangements are used in combination with other popular reactions such as ring‐closing metathesis, Suzuki coupling, Diels–Alder reaction, and retro‐Diels–Alder reaction. To this end, we prepared polycycles (e.g., cyclophanes, cage molecules), heterocycles (e.g., oxepins, azapins), carbocycles, and spirocycles with the use of the above protocol. Abstract : It rings true : Here, we review several methods toward the synthesis of a wide range of functional molecules by employing the Claisen rearrangement in combination with other powerful methods such as metathesis and Suzuki coupling.